2006
DOI: 10.1007/s00253-006-0502-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of a thermostable sarcosine oxidase (SOX) from Bacillus sp. in Escherichia coli

Abstract: A heat-stable sarcosine oxidase produced by Bacillus sp. BSD-8 (SOX) had been studied and its complete gene sequence, which contained 1,164 bp nucleotides and encoded a protein of 387 amino acids, was obtained by DNA Walking method. The sox gene was cloned and functionally overexpressed in E. coli and the recombinant SOX (rSOX) was purified to homogeneity, its properties was studied and compared with the wild type of SOX. The rSOX as well as SOX was stable at 60 degrees C and at pH 7.0 approximately 10.0, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The optimal pH of the sequential reaction was 7.5. This result is in good agreement with previous studies that demonstrated the optimal pH of HRP and SOX to be 7 and 8.5, respectively (Chance and Maehly, 1955[ 11 ]; Guo et al, 2006[ 15 ]). Precision study exhibited the high reproducibility and repeatability of the assay suggesting that our method is potentially suitable for sarcosine determination in urine under given concentration range.…”
Section: Discussionsupporting
confidence: 93%
“…The optimal pH of the sequential reaction was 7.5. This result is in good agreement with previous studies that demonstrated the optimal pH of HRP and SOX to be 7 and 8.5, respectively (Chance and Maehly, 1955[ 11 ]; Guo et al, 2006[ 15 ]). Precision study exhibited the high reproducibility and repeatability of the assay suggesting that our method is potentially suitable for sarcosine determination in urine under given concentration range.…”
Section: Discussionsupporting
confidence: 93%
“…At present, most enzymes applied in the clinical test are used in solution, and most proteins, including this enzyme, are relatively unstable when dissolved in aqueous solution. Therefore, for the enzymatic examination application, research was undertaken to search for a thermostable enzyme (Guo et al 2006;Huang et al 1998;Zhou et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that translational errors could be reduced via optimizing bases in the host strain (Vincentelli and Romier 2013). After gene optimization, the detectable SOX activity was improved by 33.5 % comparing to original gene expression in E. coli (Guo et al 2006). In the requisite induction process of fermentation phase, some induction toxicity for the cell growth was caused by improper induction condition.…”
Section: Discussionmentioning
confidence: 94%
“…1b. The detectable SOX activity reached 1,521 U/L, which was improved by 33.5 % comparing to original gene expression in E. coli (Guo et al 2006). …”
Section: Codon Optimization For Weakening Expression Suppressionmentioning
confidence: 96%
See 1 more Smart Citation